2019
DOI: 10.1080/23746149.2019.1664319
|View full text |Cite
|
Sign up to set email alerts
|

The rise of flexible electronics in neuroscience, from materials selection to in vitro and in vivo applications

Abstract: Neuroscience deals with one of the most complicate system we can study: the brain. The huge amount of connections among the cells and the different phenomena occurring at different scale give rise to a continuous flow of data that have to be collected, analyzed and interpreted. Neuroscientists try to interrogate this complexity to find basic principles underlying brain electrochemical signalling and human/animal behaviour to disclose the mechanisms that trigger neurodegenerative diseases and to understand how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 172 publications
(176 reference statements)
0
8
0
Order By: Relevance
“…with desired properties (e.g., signal transduction, amplification, multiplexing, etc.) to achieve a complex, integrated biointerface system (Maiolo et al, 2019 ; Zhang et al, 2020 ). Organic semiconductors provide unique advantages of mechanical compliance, biodegradability, and stretchability.…”
Section: Electrode Materialsmentioning
confidence: 99%
“…with desired properties (e.g., signal transduction, amplification, multiplexing, etc.) to achieve a complex, integrated biointerface system (Maiolo et al, 2019 ; Zhang et al, 2020 ). Organic semiconductors provide unique advantages of mechanical compliance, biodegradability, and stretchability.…”
Section: Electrode Materialsmentioning
confidence: 99%
“…BCI-based forehead EEGs have also been developed to assess sleep quality and can also be used as a depression treatment screening system, providing new possibilities for the treatment and evaluation of stroke patient sleep and depression risk [ 54 ]. Future efforts to improve BCI for neurorehabilitation include the development of “flexible electronics” [ 55 ] that can provide a flexible hardware platform for signal amplification to achieve closed-loop interaction, in addition to precise sensing functions. The advantages and disadvantages of BCI are summarized in Table 4 .…”
Section: Brain-computer Interface (Bci)mentioning
confidence: 99%
“…Usually, devices with a total thickness in the range of few microns can guarantee a certain degree of stretchability and higher level of conformability, even for implants composed of hybrid materials, like polyimide, and active inorganic films, like metals or silicon semiconductors. [138][139][140][141] Indeed, thin devices may be a suitable strategy to minimize the impact of the implant on brain tissue. In line with this evidence, in a recent work, Luan et al [142] demonstrated that ultraflexible nanoelectronic thread electrodes enable glial scar-free implant integration with impedances, noise levels, single-unit recording yields, and signal amplitudes that are stable up to 3.5 months implantation.…”
Section: Astrogliosis and Gliopathologiesmentioning
confidence: 99%